Efficacy of anastrozole after tamoxifen in early breast cancer patients with chemotherapy‐induced ovarian function failure. Issue 1 (16th January 2019) - van Hellemond, Irene E.G.; Vriens, Ingeborg J.H.; Peer, Petronella G.M.; Swinkels, Astrid C.P.; Smorenburg, Carolien H.; Seynaeve, Caroline M.; van der Sangen, Maurice J.C.; Kroep, Judith R.; de Graaf, Hiltje; Honkoop, Aafke H.; Erdkamp, Frans L.G.; van den Berkmortel, Franchette W.P.J.; et al.
Abstract : The DATA study (NCT00301457) compared 6 and 3 years of anastrozole in postmenopausal women with hormone receptor‐positive early breast cancer after 2–3 years of tamoxifen. Patients with chemotherapy‐induced ovarian function failure (CIOFF) were also eligible, but could be at risk of ovarian function recovery (OFR). The current analysis compared the survival of women with CIOFF with definitely postmenopausal women and examined the influence of OFR on survival. Therefore, we selected patients from the DATA study aged 45–57 years at randomization who had received (neo)adjuvant chemotherapy. They were classified by reversibility of postmenopausal status: possibly reversible in case of CIOFF ( n = 395) versus definitely postmenopausal ( n = 261). The former were monitored by E2 measurements for OFR. The occurrence of OFR was incorporated as a time‐dependent covariate in a Cox‐regression model for calculating the hazard ratio (HR). We used the landmark method to calculate residual 5‐year survival rates. When comparing CIOFF women with definitely postmenopausal women, the survival was not different. Among CIOFF women with available E2 follow‐up values ( n = 329), experiencing OFR ( n = 39) had an unfavorable impact on distant recurrence‐free survival (HR 2.27 [95% confidence interval [CI] 0.98–5.25; p = 0.05] and overall survival (HR 2.61 [95% CI 1.11–6.13; p = 0.03]). After adjusting for tumor features, the HRs became 2.11 (95% CI 0.89–5.02; p = 0.09) and 2.24 (95% CI 0.92–5.45; p = 0.07), respectively. The residual 5‐year rate for distant recurrence‐free survival was 76.9% for women with OFR and 92.1% for women without OFR, and for 5‐year overall survival 80.8% and 94.4%, respectively. Women with CIOFF receiving anastrozole may be at increased risk of disease recurrence if experiencing OFR. Abstract : What's new? In postmenopausal women with hormone receptor‐positive breast cancer, aromatase inhibitors (AIs) can prevent disease recurrence and improve survival better than tamoxifen. However, AI‐monotherapy should not be used in premenopausal women, as it can stimulate the estradiol production. Here, the authors investigated the effect of the AI anastrozole after prior tamoxifen in women with chemotherapy‐induced ovarian function failure (CIOFF) versus postmenopausal women. The Survival was comparable for definitely postmenopausal women and those with CIOFF. However, women with CIOFF whose ovarian function returned had a poorer survival, despite regular monitoring of the estradiol levels.